Complementary feeding practices: Current global and regional estimates. (15th October 2017) - White, Jessica M.; Bégin, France; Kumapley, Richard; Murray, Colleen; Krasevec, Julia
Abstract: Insufficient quantities and inadequate quality of complementary foods, together with poor feeding practices, pose a threat to children's health and nutrition. Interventions to improve complementary feeding are critical to reduce all forms of malnutrition, and access to data to ascertain the status of complementary feeding practices is essential for efforts to improve feeding behaviours. However, sufficient data to generate estimates for the core indicators covering the complementary feeding period only became available recently. The current situation of complementary feeding at the global and regional level is reported here using data contained within the UNICEF global database. Global rates of continued breastfeeding drop from 74.0% at 1 year of age to 46.3% at 2 years of age. Nearly a third of infants 4–5 months old are already fed solid foods, whereas nearly 20% of 10–11 months old had not consumed solid foods during the day prior to their survey. Of particular concern is the low rate (28.2%) of children 6–23 months receiving at least a minimally diverse diet. Although rates for all indicators vary by background characteristics, feeding behaviours are suboptimal even in richest households, suggesting that cultural factors and poor knowledge regarding an adequate diet for young children are important to address. In summary, far too few children are benefitting from minimum complementary feeding practices. Efforts are needed not only to improve children's diets for their survival, growth, and development but also for governments to report on progress against global infant and young child feeding indicators on a regular basis.